KOMUNIKASI DAKWAH DENGAN QOULAN MASYSURA DI INSTAGRAM NU ONLINE JAWA TIMUR (@nuonlinejatim): Kajian Feminisme dalam Kacamata Islam - Marzuqi, Muhammad Ganda; Faizatul Mukarromah; Ilham Maulana Yusup; Moh. Ali Aziz (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2024)
The gender issue in Indonesia remains a major concern to this day, especially among women's activists who advocate for the importance of gender equality. Efforts to achieve this equality have been carried out through women's empowerment, which is done through various training and seminars on gender. Da'wah communication has six principles, one of which is Qaulan Maysura (words that are easy to understand) as mentioned in Surah Al-Isra’ verse 28. The live broadcast of the lecture titled "Feminism in the Islamic Perspective" on the Instagram account @nuonlinejatim, presented by Ning Uswah Syauqi, provides the understanding that Islam has long addressed gender equality through related verses in the Qur'an. This research uses a descriptive qualitative approach with discourse analysis proposed by Norman Fairclough. Discourse analysis consists of three dimensions: text, discourse practice, and sociocultural practice. The da’wah communication by Ning Uswah Syauqi, based on the analysis, falls into the Qaulan Maysura category, with the material presented based on Qur'anic verses and credible sources, incorporating simple examples so that the material can be easily understood by the audience (mad’u).